2022
DOI: 10.1111/cdev.13737
|View full text |Cite
|
Sign up to set email alerts
|

Relational language influences young children’s number relation skills

Abstract: Relational language is thought to influence mathematical skills. This study examines the association between relational language and number relation skills—knowledge of cardinal, ordinal, and spatial principles—among 104 U.S. kindergartners (5.9 years; 44% boys; 37% White, 25% Black, 14% Asian, 24% other) in the 2017–2018 academic year. Controlling for general verbal knowledge, executive function, and counting and number identification skills, relational language predicted later number relation skills, specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Mastery of spatial language terms thus does not seem to be of primary relevance for grasping absolute numerical magnitudes or positions of numbers in the number sequence, at least not in the age group investigated in this study. Instead, its relevance for relative numerical magnitude understanding is also underlined by the findings of a recent study showing that relational language skills are associated with number relation skills (Chan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mastery of spatial language terms thus does not seem to be of primary relevance for grasping absolute numerical magnitudes or positions of numbers in the number sequence, at least not in the age group investigated in this study. Instead, its relevance for relative numerical magnitude understanding is also underlined by the findings of a recent study showing that relational language skills are associated with number relation skills (Chan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that no general language or cognitive skills were measured as control variables in the present study. Associations between spatial language skills and numerical skills have, however, been reported to be significant in previous studies after controlling for general language or cognitive skills (see e.g., Bower et al, 2020;Chan et al, 2022). As such, we chose to assess more specific numerical and spatial control variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical language is also distinct from specific mathematical content, such as the meaning of individual number words (e.g., cardinality; Peng et al, 2020; Purpura et al, 2019). Previous research has shown that children’s mathematical language performance relates to their numerical skills and broader mathematics achievement in preschool (Chan et al, 2019; Hassinger-Das et al, 2015; Hornburg et al, 2018; Purpura & Logan, 2015). For example, Hornburg et al (2018) showed that 3- to 6-year-old preschoolers’ mathematical language significantly predicted their performance on tasks of verbal counting, numeral knowledge, cardinality, and story problems, controlling for age, gender, and parental education.…”
Section: Executive Functioningmentioning
confidence: 99%
“…One possible explanation for the close association between FMS and the learning of academic and cognitive skills is the fact that especially complex FMS tasks activate the same brain areas as complex cognitive tasks, resulting in a co-activation of these brain areas (Diamond, 2000 ). Furthermore, these effects may be mediated through an increase in executive functions—inhibition in particular—following FMS practice, which might then be reflected as improved cognitive and academic skills (e.g., ability to inhibit irrelevant information during given tasks; Chan et al, 2022 ; Pesce et al, 2021 ). In light of previous research, it is plausible that combining the learning of EN with FMS practice may result in long-term improvements in EN.…”
Section: Introductionmentioning
confidence: 99%